KONSTRUKSI SOSIAL DALAM PERKAWINAN IDEAL ETNIS BATAK TOBA DI MEDAN SUNGGAL - Sagala, Unedo yuda Syahputra; Fimansyah, Wira (Sociology of Religion Study Program, Faculty of Social Sciences, North Sumatra State Islam, 2024)
This research aims to determine the factors that Toba Batak ethnics are not allowed to marry from different ethnic groups, to find out the perception of the young generation of Toba Batak ethnic groups regarding marriages of different ethnicities and to determine the impact of recommendations on the young generation of Toba Batak ethnic groups who have relationships with different ethnic groups and the younger generation who do not yet have a partner. It is prohibited to marry people of different ethnicities at STM PHP, Medan Sunggal District. The research method used is a qualitative research method with a descriptive approach. Data collection techniques were obtained from observation, interviews and documentation using data analysis techniques in the form of data collection, data reduction, data presentation and drawing conclusions. The results of the research show that the Toba Batak ethnic community wants their offspring to marry members of their same ethnic group and construct their offspring not to choose partners outside the Toba Batak ethnic group, this is due to the parents' desire for an ideal marriage according to the Toba Batak ethnic point of view itself because it is to maintain the line. of native Toba Batak descent, the experience of families marrying from different ethnicities and experiencing conflict, resulted in parents urging their offspring to be wise in choosing partners and those from the Toba Batak ethnic group. The social construction applied by parents to the Toba Batak ethnic group has been going on since since the time of their ancestors, the Toba Batak people still carry out this social construction to obtain the ideal marriage from the perspective of the Toba Batak ethnic group